IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMAN 8 SURABAYA: English - Mokamat Fiki Siyam Romandon; Jatiningsih , Oksiana (Universitas Negeri Surabaya (Unesa), 2025)
This study describes the implementation of the Pancasila Student Profile Strengthening Project (P5) as a response to the evolving era that drives modernization in various aspects of life. The 2013 Curriculum was subsequently revised into the Merdeka Curriculum, which incorporates P5 as a means for students to understand societal issues, take real action, and make a positive impact according to their developmental stages and needs. This research is a descriptive qualitative study, drawing data from the vice principal for curriculum, P5 coordinating teachers for grades X and XI, and students from both levels. Conducted during the first semester of the 2023/2024 academic year (August–September 2023), the study employed observation, interviews, and documentation, with data validity ensured through source and methodological triangulation. Findings show that P5 implementation at SMAN 8 Surabaya followed the stages of planning, execution, assessment, evaluation, and follow-up. Each phase involved collaboration among teachers, students, and external stakeholders. Students actively engaged in group work, communication, and meaningful social interaction. Projects such as creative dance and cultural theater strengthened students' understanding of local and national values, while fostering key character traits like cooperation, tolerance, independence, and critical thinking. Assessment was conducted holistically through observation, journals, portfolios, and rubrics aligned with the Pancasila Student Profile dimensions. Vygotsky’s constructivist theory was reflected in the use of Zone of Proximal Development (ZPD), where teachers and peer tutors provided scaffolding to support students' development from actual to potential competence.